Influenza A/Hong Kong/156/1997(H5N1) virus NS1 gene mutations F103L and M106I both increase IFN antagonism, virulence and cytoplasmic localization but differ in binding to RIG-I and CPSF30 - Dankar, Samar K; Miranda, Elena; Forbes, Nicole E; Pelchat, Martin; Tavassoli, Ali; Selman, Mohammed; Ping, Jihui; Jia, Jianjun; Brown, Earl G (Université d'Ottawa | University of Ottawa, 2013)
The genetic basis for avian to mammalian host switching in influenza A virus is largely unknown. The human A/HK/156/1997 (H5N1) virus that transmitted from poultry possesses NS1 gene mutations F103L + M106I that are virulence determinants in the mouse model of pneumonia; however their individual roles have not been determined. The emergent A/Shanghai/patient1/2013(H7N9)-like viruses also possess these mutations which may contribute to their virulence and ability to switch species.